DEVELOPMENT OF INTERACTIVE MULTIMEDIA-BASED LEARNING MEDIA FOR SOCIAL STUDIES SUBJECTS AT SMP NEGERI 2 GENDING PROBOLINGGO - Dimas Ghimby; anindya fajarini (SOLIDARITY: Journal of Social Studies, 2022)
This research aims to (1) develop interactive multimedia-based learning media in IPS class VII subjects at SMPN 2 Gending in the 2019/2020 school year, (2) to know the feasibility of interactive multimedia-based learning media in IPS class VII subjects in SMPN2 Gending in 2019/2020 school year. The research method used is research and development (R&D). This research adopted ADDIE development model with five stages namely; Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of three experts namely; material experts, media experts, and social studies teachers. Data collection techniques using questionnaires and tests. Data were analyzed using descriptive analysis techniques. Based on the results of the study, it can be concluded that the feasibility of interactive multimedia-based learning media from the validation results of the material expert team, media and social studies teachers is good and student responses are very good. Thus, interactive multimedia-based learning media is feasible to be used as a learning medium for class VII students at SMPN 2 Gending.